Increased Vasoactive Intestinal Peptide (VIP) in polycystic ovary syndrome patients undergoing IVF - Sallicandro, Luana; Gliozheni, Elko; Feudi, Davide; Sabbatini, Paola; Pellegrino, Roberto Maria; Alabed, Husam B. R.; Baldini, Domenico; Gerli, Sandro; Alviggi, Carlo; Cascardi, Eliano; Cicinelli, Ettore; Malvasi, Antonio; et al. (Frontiers in Endocrinology, 2024)
Polycystic ovary syndrome (PCOS) is a common multifactorial and polygenic disorder of the endocrine system, affecting up to 20% of women in reproductive age with a still unknown etiology. Follicular Fluid (FF) represents an environment for the normal development of follicles rich in metabolites, hormones and neurotransmitters, but in some instances of PCOS the composition can be different. Vasoactive intestinal peptide (VIP) is an endogenous autonomic neuropeptide involved in follicular atresia, granulosa cell physiology and steroidogenesis. Our ELISA and metabolomic results show: i) an increased concentration of VIP in follicular fluid of PCOS patients (n=9) of about 30% with respect to control group (n=10) (132±28 pg/ml versus 103±26 pg/ml, p=0,03) in women undergoing in vitro fertilization (IVF), ii) a linear positive correlation (p=0. 05, r=0.45) between VIP concentration and serum Anti-M llerian Hormone (AMH) concentration and iii) a linear negative correlation between VIP and noradrenaline metabolism. No correlation between VIP and estradiol (E2) concentration in follicular fluid was found. The functional role of VIP as noradrenergic modulator in ovarian physiology and PCOS pathophysiology was discussed.